Implementation Of Using The Microsoft Office Excel Application For Simple Cash Flow Recording For Msmes Fostered By Ns Creative House - Heni Rohaeni; Murti Wijayarti; Tyna Yunita; Julianto Sihar Pardamean (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Many companies use bookkeeping, but MSMEs are also in dire need of bookkeeping in their business. Bookkeeping does not have to be complicated and confusing. Simple bookkeeping is enough for small businesses to know the profit and loss earned. This research is intended to assist MSMEs in designing appropriate steps to be taken in the future and minimizing losses through the preparation of good bookkeeping using Microsoft Office Excel Applications. The crucial problem often found in MSMEs, especially the fostered partners of NS Creative House, is the problem of financial management. Due to the lack of ability of MSMEs owners to manage and record business finances, financial income and expenditure are not recorded clearly and neatly. After participating in this training, MSMEs fostered partners to become able to implement Microsoft Office Excel applications in doing simple records, which significantly affects business development. Through bookkeeping, MSMEs owners can see the condition and development of the business, including the company's profits and losses. With this, bookkeeping can be used as a benchmark for future business strategies.Keywords: Implement